Prophetic Hard Skills and the Competence of Bangladeshi Madrasha Graduates: Evaluation and Recommendations (Jagannath University Journal of Arts, 2026)
Bangladeshi madrasahs, emphasizing the practical skills demonstrated by Prophets as outlined in Islamic texts. While traditional madrasah education in Bangladesh focuses predominantly on spiritual and religious studies, it neglects essential hard skills necessary for modern job markets. Similarly, madrasa graduates believe that worldly work diminishes religious dignity, while the lack of modern education deprives them of skills; mosque service is still a duty. But, prophetic examples highlight the importance of hard skills such as agriculture, maritime engineering, textile technology, and military strategy, which were crucial for self-sufficiency and effective leadership. The study identifies several challenges faced by madrasah graduates, including ideological divisions within Islamic factions, conventional teaching methods, and resistance to integrating scientific knowledge. It also addresses misconceptions and prejudices against worldly skills, often perceived as contrary to Islamic teachings. Despite efforts to modernize, current madrasah graduates struggle with limited practical skills, which affects their employability and economic self-sufficiency. Through a comprehensive review of literature and primary data from discussions with madrasah graduates, the paper proposes recommendations for curriculum integration, teacher training, career counseling, and community engagement. These measures aim to align madrasah education with contemporary job market requirements and the prophetic model of combining both spiritual and practical knowledge. The paper concludes that addressing these issues is vital for preparing madrasah graduates to thrive in the modern world while upholding Islamic values.Jagannath University Journal of Arts, v-15, i-01, 2025:p101-112